Evaluation of variability in Striga aspera, Striga hermonthica and their hybrids using morphological characters and random amplified polymorphic DNA markers - Aigbokhan, E.I.; Berner, D.K.; Musselman, L.J.; Mignouna, Hodeba D. (2000)
Striga aspera and Striga hermonthica are recognized as separate species, but their close morphological similarity causes difficulty in distinguishing between them in areas where they coexist in Africa. In this study, crosses between the species were made using randomly selected morphologically typical parental plants collected from different locations in Nigeria. Genetic analysis of both species and their reciprocal F1hybrids were determined using cluster analysis of DNA pro Æles derived from genetic polymorphism (RAPD)-polymerase chain reaction (PCR) markers. Principal component and hierarchical cluster analyses were used to separate parental and hybrid populations based on 13 morphological characteristics. Morphological data from wild samples of both species were compared with the hand-pollinated parental, F1and F2hybrids, and back-crosses. Results showed that S. Aspera and S. hermonthica were genetically and morphologically distinct. Morphological and genetic analyses revealed two major clusters: a S. Aspera cluster and S. hermonthica cluster. Genetically, the F1hybrids showed closer a unity to their maternal parents, while morphologically, the F1hybrids formed distinct clusters intermediate to the parents. Most F2plants and back-crosses were morphologically similar to S. hermonthica. Comparative morphological analysis of wild and hand-pollinated populations showed some samples from the wild clustered with the hybrids, suggesting that hybrids may exist in nature.